Ethical marketing and the new consumer - Arnold, Chris (Chichester, U.K. : Wiley, 2009)
Ethical marketing isn't just about environmentalism, it's far bigger than that. This book challenges a lot of conventional thinking and introduces you to a wider range of ethics and the many types of ethical consumers. --from publisher description.
The power of brand ethos -- Ethical : reality or a brand image? -- Churn and the disposable society -- Bad tasting medicine -- It's not what you say but what you do -- Brand terrorism -- Survival and security -- Engaging the consumer, sharing responsibility -- Finding reasons to buy -- Research and surveys -- The business and religion of ethics -- Fairtrade -- Food waste and recycling -- Recycling for resale -- Turning recycling into good marketing -- The ethical sphere -- Language and persuasion -- How to be a creative marketer -- Fat and fit : obesity and health -- Selling ethical behaviour -- From brand values to brand value -- Fast fashion -- Washing green -- Green insurance and finance.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2021. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Marketing -- Moral and ethical aspects; New Age consumers; Electronic books